The early reception of the Book of Isaiah - De Troyer, Kristin 1963-; Schmitz, Barbara 1975-; Walter de Gruyter GmbH & Co. KG (Berlin Boston De Gruyter, 2018)
Frontmatter -- Table of Contents -- List of Abbreviations -- Introduction / Schmitz, Barbara / De Troyer, Kristin -- An Intertextual Dialogue between the Book of Isaiah and the Book of 1 Maccabees: On Judean Leadership / Sweeney, Marvin A. -- The Concept of the City in the Book of Isaiah and in the Deuterocanonical Literature / van Wieringen, Archibald L. H. M. -- Divine and Divinely Sanctioned Violence in the Book of Isaiah and the Deuterocanonical Literature / Hibbard, J. Todd -- The Messiah and the 'End of Days' in the Book of Isaiah and in the Deuterocanonical Literature / Fried, Lisbeth S. / Mills, Edward J. -- The Temple in the So-Called Jewish Romances in the Deuterocanonical Literature: Judith, Tobit, and Esther / Middlemas, Jill -- Old Greek Isaiah 1:13: Early Evidence for the "Great Day" as a Name for Yom Kippur? / Wagner, J. Ross -- The Book of Isaiah, the Wisdom of Solomon and the Fathers: An Exploration of the Textual History and Concepts / Elliott, Mark W. -- List of Contributors -- Indices
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, Textual; Bible -- Criticism, Textual; Bible -- Criticism, Textual; Intertextuality in the Bible; RELIGION / Biblical Criticism & Interpretation / Old Testament; Religion / Judaism / History; LITERARY CRITICISM / Jewish; Deuteroncanonical books; RELIGION / General; Isaiah; Old Testament; Hebrew Bible; Deuterocanonical books; Konferenzschrift -- 2016 -- San Antonio, Tex